Validation and Application of LC-MS/MS Method for Quantification of Cyanogenic Glucosides in Domestic Commercial Food Samples - Hana, Park; CHO, YOESEPH; wooyeon, Jung; Heo, Soohyun; Yong-Sun Bahn; SON, Jung hyun (The 70th Biannual Conference of The Korean Society of Analytical Sciences, 2023)
Cyanogenic glucosides are secondary plant metabolites found in many plant foods, including fruits, vegetables, and grains. These compounds are not harmful in themselves, but when degraded by enzymes they release hydrogen cyanide, which can be toxic to humans and animals. There is therefore a need for research into the cyanogenic glucosides content of commonly consumed foods. This validated method for the simultaneous determination of four cyanogenic glucosides, including lotaustralin, prunasin, taxiphyllin, and dhurrin using ultra-high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) and solid-liquid extraction (SLE) is a useful tool for accurate identification and quantification of intact cyanogenic glucosides content in foods. The method was evaluated in terms of linearity, the limit of detection, the limit of quantification, accuracy, and precision. It was successfully applied to the quantification of intact cyanogenic glucosides in 151 domestic commercial food samples, demonstrating its practicality and utility in food safety assessment. It showed that in food samples analyzed, lotaustralin was present at concentrations of 0.040-41.13 mg/kg, prunasin at 0.15-8.77mg/kg, taxiphyllin at 0.019-0.28mg/kg, and dhurrin at 0.043-0.64mg/kg. These results provide important information for the assessment of potential risks to human health associated with the consumption of foods containing glucoside cyanide. The validated method can also be used for the monitoring of the glucoside cyanide content of foods and the development of appropriate food safety strategies.